Enhancement of molecular weight reduction of natural rubber in triphasic CO2/toluene/H2O systems with hydrogen peroxide for preparation of biobased polyurethanes - Alif Duereh; Chokchai Boonchuay; Piyapong Buahom; Surat Areerat (My University, 2018)
Abstract Molecular weight reduction of natural rubber (NR) with hydrogen peroxide (H 2 O 2 ) oxidizing agent is limited in biphasic water-toluene systems that is attributed to mass transfer. In this work, CO 2 was applied to the (aqueous H 2 O 2 )-(toluene-NR) systems with the objective of improving reaction efficiency. Experiments were performed on the reaction system with CO 2 at 12 MPa and at reaction temperatures and times of 60°C–80°C and 1 h–10 h to evaluate the reaction kinetics. CO 2 could enhance the NR molecular weight reduction by lowering the activation energy (from 121 kJ·mol −1 to 38 kJ·mol −1 ). The role of CO 2 in the reaction system seems to be the formation of oxidative peroxycarbonic acid intermediate and promotion of mass transport due to the reduction in the toluene-NR viscosity and interfacial tension. The epoxidized liquid NRs ( M ̅ n =4.9×10 3 g·mol −1 ) obtained from NR molecular weight reduction was further processed to prepare hydroxyl telechelic NR ( M ̅ n =1.0×10 3 g·mol −1 ) and biobased polyurethane.
Keywords: Oxidizing agent; Carbon dioxide utilization in catalysis